Geographical And Socioeconomic Analysis In Peninsular Malaysia - Fam, Soo Fen; Ismail, Noriszura; Jemain, Abdul Aziz (Medwell Journals, 2017)
This study aims to develop a pioneer composite area-based index of socioeconomic deprivation, namely the General Index of Deprivation (GID) using Principal Component Analysis (PCA). The proposed GID which is based on combined resources of census data, administrative registration data, vital statistics and insurance data of eighty-one Administrative Districts (ADs) in Peninsular Malaysia in 2000 can be used to provide a greater understanding and interpretation of the distribution of socio-economic patterns across the ADs. This study also measures the overall and the local clustering in socio-economic deprivation across ADs in Peninsular Malaysia using Global and Local Moran’s I. Further, visualizations of the patterns of socio-economic deprivation based on the proposed GID and the locations of spatial clusters based on the Local Moran’s I are implemented by using choroplate maps. The results of GID indicate that the ADs can be ranked and classified into four quartiles; the most affluent, the moderately affluent, the moderately deprived and the most deprived. The majority of affluent areas were located in the westcoast of Peninsular Malaysia whereas the most deprived areas were mainly scattered in the Northeast of Peninsular Malaysia. The results of Global Moran’s I suggests significant and positive global spatial autocorrelation across spatial weights of the ADs. In addition, the results on Local Moran’s I show strong spatial disparities of socioeconomic deprivation in several ADs, indicating the importance of considering geographic localization and spatial condition of each AD for allocating resources and implementing efficient policies in Peninsular Malaysia.